Incidence of macular hole in patients undergoing pars plana vitrectomy for submacular hemorrhage - Riko Matsumoto; Masashi Kakinoki; Osamu Sawada; Shumpei Obata; Yoshitsugu Saishin; Masahito Ohji (PLoS ONE, 2025)
Purpose To investigate the incidence of macular hole (MH) during pars plana vitrectomy (PPV) for submacular hemorrhage (SMH) due to either retinal arterial macroaneurysm (RAM) rupture or age-related macular degeneration (AMD). Methods We retrospectively evaluated 47 eyes of 47 patients with SMH due to RAM rupture or AMD who underwent PPV. The presence or development of MHs was confirmed intraoperatively by the surgeon. We compared the incidence of MH between the RAM and AMD groups. Results In the RAM group, a MH was found in five of 28 (17.9%) eyes, and a MH was developed in three eyes by the surgical procedure. In the AMD group, there was no MH. All MHs were identified intraoperatively and closed by the same surgical procedure. In the RAM group, subretinal tissue plasminogen activator (t-PA) injection was performed in 12 eyes. Of the 12 eyes, two developed an MH before t-PA subretinal injection. Of the remaining 10 eyes, four (40%) developed an MH intraoperatively or postoperatively. Conclusion MHs are complications of PPV for SMH that occur more frequently in patients with SMH due to RAM rupture than in patients with SMH due to AMD.